2020
DOI: 10.1038/s41598-020-76316-7
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of phenolic compounds in meadow soils

Abstract: The aim of the research has been to determine the role of phenolic compounds in the processes of transformations of organic matter in meadow soils, leading to the formation of humic substances. The research has been performed based on the plant material and soil sampled from Europe’s unique complex of permanent grasslands irrigated continuously for 150 years applying the slope-and-flooding system, the Czerskie Meadows. Phenolic compounds were isolated from the plant material samples (hay, sward and roots) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The readily available, dissolved forms of phenolic compounds (aqueous extracts, WE) made up only a small part of the potential pool of antioxidants in the topsoil horizons of the studied soils. However, their role should not be marginalized, as these compounds, present by definition in low concentrations in soil solution, participate in many redox processes, including the formation of humic substances 19 . TAC in WE ranged from 5 to slightly over 21 µg g −1 for abandoned soils and farmlands to about 114 µg g −1 for forest soils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The readily available, dissolved forms of phenolic compounds (aqueous extracts, WE) made up only a small part of the potential pool of antioxidants in the topsoil horizons of the studied soils. However, their role should not be marginalized, as these compounds, present by definition in low concentrations in soil solution, participate in many redox processes, including the formation of humic substances 19 . TAC in WE ranged from 5 to slightly over 21 µg g −1 for abandoned soils and farmlands to about 114 µg g −1 for forest soils.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies imply that most of the antioxidants in soil can be found among the humic substances 15 18 . This was evaluated by Ziółkowska et al 19 ., who determined the important role of phenolic compounds in the processes of organic matter transformations in meadow soils, leading to the formation of humic substances. What is more, phenolics are considered more resistant to decomposition in soils compared to other organic matter sources, and thus have often been regarded a slow carbon pool in soil dynamics models 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Just like straw, (lucerne) hay has been shown to increase nest building and reduce stereotypical behavior prior to farrowing (Edwards et al, 2019). Compared to straw, good-quality hay might provide additional nutritional benefits for lactating sows, including higher metabolizable energy and crude protein levels (Kamphues, 2004) as well as a high content of secondary plant substances (Ziolkowska et al, 2020), contributing to pigs' health. Hay might also be preferred as enrichment material over straw by young piglets as it is softer and therefore easier to chew.…”
Section: Introductionmentioning
confidence: 99%
“…They also contribute to form body structures (Wigglesworth, 1988) and coloration (Krishnan, 1951) in plant and animal bodies. Phenolic acids are considered as important precursors of humic substances in soils (Ziolkowska et al, 2020). They play multiple roles in soil formation and pedogenesis, that can directly influence the recycling of minerals as well as organic matter dynamics (Seneviratne and Jayasinghearachchi, 2003), by producing organic metal complexes, and also serve to increase the availability of micro and macro nutrients (Micales, 1997).…”
Section: Introductionmentioning
confidence: 99%